Proceedings of the 3rd International Symposium on Visual Information Communication 2010
DOI: 10.1145/1865841.1865844
|View full text |Cite
|
Sign up to set email alerts
|

The promise of zoomable user interfaces

Abstract: Zoomable User Interfaces (ZUIs) have received a significant amount of attention in the 17 years since they were introduced. They have enjoyed some success, and elements of ZUIs are widely used in computers today, although the grand vision of a zoomable desktop has not materialized. This paper describes the premise and promise of ZUIs along with their challenges. It describes design guidelines, and offers a cautionary tale about research and innovation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…ZUIs have been shown to significantly improve users' ability to find information across multiple layers of data (Helt et al, 2009;Bederson, 2010), and animated navigation transitions have been shown to increase user task performance, even taking into account the time of the transitions themselves (Klein and Bederson, 2005). A custom ZUI framework was created to handle zoom transitions between data visualization modules in ePlant.…”
Section: Resultsmentioning
confidence: 99%
“…ZUIs have been shown to significantly improve users' ability to find information across multiple layers of data (Helt et al, 2009;Bederson, 2010), and animated navigation transitions have been shown to increase user task performance, even taking into account the time of the transitions themselves (Klein and Bederson, 2005). A custom ZUI framework was created to handle zoom transitions between data visualization modules in ePlant.…”
Section: Resultsmentioning
confidence: 99%
“…Gaucho is a zoomable user interface [54], i.e., the pampas can be panned and zoomed, enabling developers to fully customize different perspectives on the system under construction. A session can include one or more pampas, to provide multiple perspectives on the same system.…”
Section: The Pampasmentioning
confidence: 99%
“…Several tools have adapted the zoomable user interfaces paradigm [1,2] specifically for presentation support [7,11,17]. CounterPoint [7] broke new ground by positioning PowerPoint slides inside a zoomable user interface.…”
Section: Related Workmentioning
confidence: 99%
“…It was previously studied how authors deal with the two paradigms when preparing for a talk [11,13], and how audiences perceive talks given in the two formats [12], but the effect on the presenter herself has not been investigated, yet. The canvas format should be especially helpful for navigations that deviate from the planned presentation delivery, e.g., in response to a question [2,7]. The presenter can quickly pan-andzoom, thereby creating impromptu overviews and showing the macrostructure of the talk to the audience.…”
Section: Introductionmentioning
confidence: 99%